(3fRgI GdfGXQ aj GdCTHGg hGdfXGFQs - (3GdMdj, GdgPdj, CHh RcQjG, fLjH GdOjf, GHf ejKe GdMdj, jMji Hf CMeO Hf jMji Hf GdMSf Hf SYjO, J(B689(3g`s ((3eMeO TajY Hf YHO GdhGMO ajQhRBHGOjs)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf(B... (3GYde Gfj UfaJ gPG GdcJGH hLeYJ ajg (B... (3hSejJg(B: (3fRgI GdfGXQ(B...s
(3BNQgG (B:s
(3hQhi eMeO Hf GdMSf GdUaGQ (B... (3Yf GHjg bGd(B: (3bGd QShd Gddg Udi Gddg Ydjg hBdg(B: (3ef TgQ(B... (3hCjeG QLd CNP aj hSW GdWQjb aCUGHg YjH adG OjI dg(B. (3Je HGdNjQ hGdSYGOIs
(3JHUQI GdeDda (B:s
(3hjYQa HGHf ejKes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B8(3, U(B135s
(3eYLe GdeDdajf(B: (3L(B4(3, U(B87s
(3EjVGM Gdecfhf(B: (3L(B2(3, U(B642s
Keywords: (3abg GdePGgH GdCNQis